2021
DOI: 10.1007/s10709-021-00113-x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and tempo of PCSK9 pseudogenizations suggest an ancient divergence in mammalian cholesterol homeostasis mechanisms

Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) plays a central role in cholesterol homeostasis in humans as a major regulator of LDLR levels. PCSK9 is an intriguing protease in that it does not act by proteolysis but by preventing LDLR recirculation from endosomes to the plasma membrane. This, and the inexistence of any other proteolytic substrate but itself could suggest that PCSK9 is an exquisite example of evolutionary fine-tuning. However, the gene has been lost in several mammalian species, and nul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…In this context, we previously observed that the loss of PCSK9 leads to higher surface levels of the LDLR in enterocytes and VLDLR in visceral adipose tissue of female, but not male mice [19]. Interestingly, PCSK9 pseudogenization in the large group of placental mammals Laurasiatheria occurred repeatedly, indicating that alteration in their cholesterol metabolism made them more susceptible to lose PCSK9 [54]. Therefore, in species lacking PCSK9, including pigs, bovines, camels, whales, bats, cats, dogs, bears and horses, it would be interesting to evaluate the functional relevance and metabolic consequences of E2-mediated shedding of liver surface LDLR.…”
Section: Discussionmentioning
confidence: 98%
“…In this context, we previously observed that the loss of PCSK9 leads to higher surface levels of the LDLR in enterocytes and VLDLR in visceral adipose tissue of female, but not male mice [19]. Interestingly, PCSK9 pseudogenization in the large group of placental mammals Laurasiatheria occurred repeatedly, indicating that alteration in their cholesterol metabolism made them more susceptible to lose PCSK9 [54]. Therefore, in species lacking PCSK9, including pigs, bovines, camels, whales, bats, cats, dogs, bears and horses, it would be interesting to evaluate the functional relevance and metabolic consequences of E2-mediated shedding of liver surface LDLR.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study revealed a dramatic difference in the patterns of PCSK9 retention and loss between the 4 major clades of placental mammals ( 288 ). Namely, the Euarchontoglires clade that includes primates, rodents, and rabbits exhibit a strong pressure for gene preservation, whereas the Laurasiatheria clade is characterized by multiple independent events that led to the loss of PCSK9 in many species, such as pigs, bovine, camels, whales, bats, cats, dogs, bears, and horses ( 289 ). The loss of PCSK9 expression in pigs, suggests that studies of cholesterol metabolism therein would be advantageous for understanding cholesterol-related human diseases, as recently reported in D374Y-PCSK9 transgenics ( 152 ) resulting in hypercholesterolemic minipigs, a porcine model of advanced coronary atherosclerosis ( 290 ).…”
Section: Discussionmentioning
confidence: 99%
“…PCSK9 is present in most vertebrates including humans, primates, and rodents, yet, has been lost in pigs, cows, camels, horses, dogs, and cats. 24 It is immediately apparent that loss of PCSK9 occurred in domesticated animals where humans were likely controlling food sources and availability. Restricting food availability can remove a potentially powerful selective force that could maintain a gene in the genome.…”
Section: Genetic Diversity and Domesticationmentioning
confidence: 99%
“…Restricting food availability can remove a potentially powerful selective force that could maintain a gene in the genome. Gene loss during domestication, 24 and a decrease in gene expression diversity have been observed in domesticated animals. 25 Often, domesticated species are, in fact, not very good at surviving in the wild without human cultivation.…”
Section: Genetic Diversity and Domesticationmentioning
confidence: 99%